Firearm Suicide as a Human Rights Priority for Prevention - Hannah S. Szlyk; Enoch Azasu; Sean Joe (Washington University Journal of Law & Policy, 2019)
In addition to being a public health crisis, firearm suicide in the United States poses an ongoing threat to human rights of U.S. residents. This article argues that the U.S. is bound to act to honor its human rights obligations in this area. The article first reviews current statistics on firearm suicide in the U.S. It then outlines how the U.S. violates internationally established human rights by adhering to its current policies regarding firearms. Finally, the article suggests priorities for policy, public health intervention, and interdisciplinary education regarding access to firearms in the U.S.
Keywords: firearm suicide; human rights; prevention; public health; firearm; guns; gun violence; international human rights